2017
DOI: 10.1016/j.bbadis.2016.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic relevance of mTOR inhibition in murine succinate semialdehyde dehydrogenase deficiency (SSADHD), a disorder of GABA metabolism

Abstract: Aldehyde dehydrogenase 5a1-deficient (aldh5a1−/−) mice, the murine orthologue of human succinic semialdehyde dehydrogenase deficiency (SSADHD), manifest increased GABA (4-aminobutyric acid) that disrupts autophagy, increases mitochondria number, and induces oxidative stress, all mitigated with the mTOR (mechanistic target of rapamycin) inhibitor rapamycin [1]. Because GABA regulates mTOR, we tested the hypothesis that aldh5a1−/− mice would show altered levels of mRNA for genes associated with mTOR signaling an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 51 publications
1
22
0
Order By: Relevance
“…Although GABA levels have been effectively quantified in platelets isolated from whole blood (Kowa et al 1992), we opted for isolation of plasma since an objective was to determine if total GABA levels might be elevated in this compartment and potentially inform GABA concentrations in whole bloodspots for eventual newborn screening of SSADHD. Moreover, since we have recently demonstrated that both GHB and GABA are significantly elevated in brain and peripheral organs (kidney, liver) of SSADH-deficient mice (Vogel et al, in revision), we assume that peripheral GABA metabolism mimics the pathway of metabolism shown in brain. The latter underscores the utility of measuring these biomarkers in peripheral tissues (plasma, red blood cells) as a surrogate for brain, or even cerebrospinal fluid, measurements.…”
Section: Methodsmentioning
confidence: 92%
“…Although GABA levels have been effectively quantified in platelets isolated from whole blood (Kowa et al 1992), we opted for isolation of plasma since an objective was to determine if total GABA levels might be elevated in this compartment and potentially inform GABA concentrations in whole bloodspots for eventual newborn screening of SSADHD. Moreover, since we have recently demonstrated that both GHB and GABA are significantly elevated in brain and peripheral organs (kidney, liver) of SSADH-deficient mice (Vogel et al, in revision), we assume that peripheral GABA metabolism mimics the pathway of metabolism shown in brain. The latter underscores the utility of measuring these biomarkers in peripheral tissues (plasma, red blood cells) as a surrogate for brain, or even cerebrospinal fluid, measurements.…”
Section: Methodsmentioning
confidence: 92%
“…Nutrient starvation is associated with dissociation of the inactive mTORC1 from the lysosomes, resulting in increased autophagy. Thus, activation of mTOR by GABA is likely to exacerbate the accumulation of aberrant mitochondria in SSADH-D by inhibiting mitophagy, suggesting that mTOR inhibition may exhibit therapeutic potential in SSADH-D. Vogel and coworkers analyzed the effect of various mTORC inhibitors in SSADH knockout mice [78,79]. They showed that the lifespan of the mice can be extended by dual inhibitors of mTORC1 and mTORC2, Torin 2, and XL-765 [79].…”
Section: Mitochondrial Dysfunction Redox Imbalance and Autophagy Dementioning
confidence: 99%
“…They showed that the lifespan of the mice can be extended by dual inhibitors of mTORC1 and mTORC2, Torin 2 and XL-765 [65]. In addition, the mTOR-independent autophagy inducing peptide tat-Beclin 1 [66] also prevented the early lethality in these mice [65]. These findings suggest that inhibition of mTOR activity and/or induction of autophagy may exhibit therapeutic potential in SSADH-D.…”
Section: Mitochondrial Dysfuntion Redox Imbalance and Autophagy Defementioning
confidence: 97%
“…Nutrient starvation is associated with dissociation of the inactive mTORC1 from the lysosomes, resulting in increased autophagy. Thus, activation of mTOR by GABA is likely to exacerbate the accumulation of aberrant mitochondria in SSADH-D by inhibiting mitophagy, suggesting that mTOR inhibition may exhibit therapeutic potential in SSADH-D. Vogel and coworkers have analyzed the effect of various mTORC inhibitors in the SSADH knockout mice [64,65]. They showed that the lifespan of the mice can be extended by dual inhibitors of mTORC1 and mTORC2, Torin 2 and XL-765 [65].…”
Section: Mitochondrial Dysfuntion Redox Imbalance and Autophagy Defementioning
confidence: 99%
See 1 more Smart Citation